In dark times, the brazilian academic production on literacy: quality assessment and scientific and social impact - Mortatti, Maria do Rosario [UNESP] (Univ Fed Sao Carlos, 2018)
In order to contribute to the critical evaluation of the quality and the scientific and social impact of Brazilian academic production on literacy, the correlation among theses/dissertations and articles on the subject in journals evaluated by CAPES is discussed. The following aspects are highlighted: in spite of the quantitative advances, it is still incipient the circulation of this knowledge as qualified production; despite the relative plurality of analytical approaches deriving from the interdisciplinary characteristic of the theme, similar objects of study and results have been reiterated, dispersing their possible social and scientific impact; it is necessary to jointly define actions for critical evaluation, aiming to the formulation and proposition of new problems and objects, discussion of scientific and social purposes, relationship with funding agencies and public policies, expansion/strengthening of discussion spaces, vehicles and ways of disseminating knowledge about the subject.
Keywords: Literacy in Brazil; Academic production; Scientific and social impact